Using Story Mapping Technique in Teaching Writing Skills at SMAN 1 Palopo - Daung Allo, Ashar; Wahibah, Wahibah; Thayyib, Magfirah (FOSTER: Journal of English Language Teaching, 2020)
The purpose of this research was to find out whether the use of story mapping technique effective to improve students’ writing recount text at the first grade of SMAN 1 Palopo. This research applied quasi experimental. The research was carried out in two classes, experimental and control classes. The population of this research was the first grade students of SMAN 1 Palopo. The samples of this research were Class X MIPA 2 as a control class and Class X IPA 3 as experimental class. The sampling technique in this research was random sampling. The instrument of this research was writing test. The writer gave pretest and posttest to the students. The data was analyzed by using SPSS 20.The result of this research showed that the use of story mapping technique in teaching writing recount text is effective. It could be seen from the result of calculation that the students’ score in experimental class which was higher than students’ score in control class. The mean score of posttest in experimental class was higher than the mean score of pretest (76.7667>61.6667). While in control class the mean score of posttest was also higher than the mean score of pretest (71.0667>67.8000). It means that there was significant difference between the students’ score in teaching writing recount text by using story mapping technique and students’ score in teaching writing recount text without using story mapping technique at the first grade of SMAN 1 Palopo.